First report of piperidone extracts as tyrosinase and α-glucosidase inhibitors from fruits of Piper retrofractum - Yodsawad, Thita; Doungwichitrkul, Titiruetai; Meemongkolkiat, Thitipan; Chanchao, Chanpen; Damsud, Thanakorn; Phuwapraisirisan, Preecha (Agriculture and Natural Resources, 2024)
Importance of the work: Piper retrofractum is used as a spice. This report is the first to identify tyrosinase and α-glucosidase inhibitors extracted from this plant. Objectives: To separate and identify the bioactive compounds from the fruits of P. retrofractum and to evaluate their tyrosinase and α-glucosidase inhibition activities. Materials & Methods: The EtOAc extract was isolated and purified using various chromatographic techniques. The structures of isolated compounds were confirmed based on their spectroscopic data. The tyrosinase and α–glucosidase inhibition activities of the isolated compounds were assessed based on a colorimetric method, using kojic acid and acarbose, respectively, as positive controls. Results: Seven known compounds were identified, named methyl piperate (1), guineensine (2), piperine (3), N-feruloyltyramine (4), (3S, 4S)-4-chloro-3-hydroxy-2-piperidin-2-one (5), 3-chloro-4-hydroxy-2-piperidone (6) and 3α,4α-epoxy-2-piperidone (7). Piperidones 5 and 6 showed tyrosinase inhibition with concentration at 50% inhibition (IC50) values of 4.91 mM and 11.0 mM, respectively, whereas the alkylamides 1–3 and phenylpropanamide 4 were not active. On the other hand, only phenylpropanamide 4 was active against maltase and sucrase with IC50 values of 0.28 mM and 0.5 mM, respectively. Piperidone 5 showed weak inhibition against both maltase and sucrase α-glucosidases, while the piperidones 6 and 7 exhibited weak inhibition against sucrase α-glucosidases. Main finding: The piperidones were more active against tyrosinase than piperine, which is representative metabolite from this plant. Further study on the inhibitory mechanism may lead to suitable applications of the extract in cosmetics.